Developing E-Comic Media for Teaching the History of the Banten Kingdom in High Schools - Johan Setiawan; Muh Taufiq Nurwansyah; Daud Yahya (STAI Hubbulwathan Duri, 2025)
History learning in Indonesian high schools often relies on conventional methods, which can reduce students’ motivation and engagement. To address this issue, this study aimed to develop an innovative e-comic as a digital learning medium for teaching the history of the Banten Kingdom. The research employed a Research and Development (RD) approach using the Sugiyono model, consisting of four stages: needs analysis, product design, expert validation, and revision. Data were collected through interviews, questionnaires, and classroom observations involving one history teacher and ten Grade X students at SMA Muhammadiyah At Tanwir Metro. The prototype was evaluated by two material experts, two media experts, and students as end users. The needs analysis revealed that existing history learning media lacked variety and technological integration, leading to low student interest. The developed e-comic integrates narrative, visuals, and interactive features, including audio and digital navigation. Validation results indicated good feasibility: material experts rated the product at 81% (very feasible) after two validation cycles, and media experts rated it at 91% (very feasible). Student responses also showed high acceptance, with most ratings falling in the “highly suitable” category. The findings suggest that e-comics can increase students’ engagement and comprehension of historical content by combining visual and textual information, in line with multimedia learning principles. The e-comic on the Banten Kingdom is valid and feasible for classroom use, with potential to enhance historical understanding and encourage the integration of technology in history education.